An immobilized hyaluronidase and its preparation method and application in preparing ultra-low molecular weight hyaluronic acid

By forming metal organic frame materials (MOFs) on three-dimensional foam metals, the problems of poor stability and waste of resources in the prior art are solved, and efficient and stable low molecular weight hyaluronate is achieved. preparation.

CN118406676BActive Publication Date: 2025-02-18JUWEI (WUXI) BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410638298.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-22
Publication Date
2025-02-18
Estimated Expiration
2044-05-22

AI Technical Summary

Technical Problem

The prior art has problems of poor stability and ease of inactivation in the preparation of low molecular weight hyaluronic acid, and traditional methods have problems of waste of resources and high production costs.

Method used

Using the method of immobilizing hyaluronidase, the hyaluronidase is immobilized in MOFs by forming metal organic frame materials (MOFs) on three-dimensional foam metal, thereby improving its stability and reusability.

Benefits of technology

The high stability and reusability of hyaluronidase are achieved, resource waste and production costs are reduced, and the preparation efficiency of low molecular weight hyaluronic acid is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118406676B_ABST
    Figure CN118406676B_ABST
Patent Text Reader

Abstract

The present application relates to the field of cosmetic technology, and specifically discloses an immobilized hyaluronidase and a preparation method thereof and an application in the preparation of ultra-low molecular weight hyaluronic acid. The present application pre-treats a three-dimensional foam metal, utilizes the metal ions therein to bind an organic ligand, and prepares a metal organic framework material MOFs material on the three-dimensional foam metal to achieve the immobilization of hyaluronidase. The three-dimensional foam metal MOFs material of the present application has an ultra-high specific surface area, provides multiple sites for the immobilization of hyaluronidase, and the immobilized hyaluronidase formed not only has a good immobilization effect, but also has a high thermal stability and a good salt tolerance after the immobilization of the hyaluronidase, and can be repeatedly used, and is suitable for application in industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of cosmetic technology, and in particular to an immobilized hyaluronidase and a preparation method thereof and an application thereof in the preparation of ultra-low molecular weight hyaluronic acid. Background Art

[0002] Hyaluronic acid (HA) is a type of viscous polysaccharide composed of D-glucuronic acid (GlcUA) and N-acetylglucosamine (GlcNAc) linked by β-1,3 glycosidic bonds and β-1,4 glycosidic bonds to form unbranched disaccharide repeating units, commonly known as hyaluronic acid. Existing studies have shown that HA of different molecular weights exhibit different biological activities. High molecular weight HA (Mr>2×10 6 ) has good viscoelasticity, moisturizing, anti-inflammatory and lubricating properties, and can be used in high-end cosmetics, ophthalmic surgery viscoelastics and intra-articular injection therapy. Medium molecular weight hyaluronic acid (Mr is 1×10 5 Up to 1×10 6 ) has good moisturizing, lubricating and drug sustained-release properties and can be widely used in cosmetics, eye drops, skin burn healing and postoperative adhesion prevention. Low molecular weight hyaluronic acid (Mr<1×10 5 ) shows very strong biological activity, inhibiting tumor spread, promoting wound healing, promoting bone and angiogenesis, immune regulation, etc., and it is easy to penetrate into the dermis and can be used as an activator of immune cells and cytokines. Small molecule hyaluronic acid has broad application prospects in food health care, cosmetics and clinical medicine.

[0003] At present, the common preparation methods of low molecular weight hyaluronic acid are physical method, chemical method and enzymatic method. The physical method mainly uses heating, mechanical shear force, ultraviolet light, ultrasound, 60Co irradiation, γ-ray radiation and other methods promote the degradation of HA. The chemical method is mainly divided into hydrolysis and oxidative degradation. The hydrolysis method is divided into acid hydrolysis (HCl) and alkaline hydrolysis (NaOH). The commonly used oxidants for oxidative degradation are sodium hypochlorite (NaClO) and hydrogen peroxide (H2O2). Both the physical method and the chemical method have certain disadvantages. For example, the heating method easily causes the low molecular weight hyaluronic acid to change color. The chemical method needs to introduce chemical reagents during the degradation process, which is easy to affect the product purification step and the properties of the final product. The biological enzymatic hydrolysis method uses specific hyaluronidase to break the glycosidic bonds between the molecular chains of high molecular weight hyaluronic acid, thereby degrading to obtain low molecular weight hyaluronic acid. The enzymatic hydrolysis method is highly efficient and specific. Using specific enzymes to enzymatically hydrolyze high molecular weight hyaluronic acid can obtain low molecular weight hyaluronic acid with concentrated molecular weight distribution and high purity. Although the enzymatic hydrolysis method is highly efficient, it has problems such as poor stability and easy inactivation, which makes the reaction conditions of the enzymatic hydrolysis method relatively harsh and not conducive to large-scale production. In addition, hyaluronidase cannot be recovered for secondary use after use, resulting in a waste of resources. Summary of the invention

[0004] The purpose of the present application is to overcome the deficiencies of the above-mentioned prior art and to provide an immobilized hyaluronidase and a preparation method thereof and an application thereof in the preparation of ultra-low molecular weight hyaluronic acid.

[0005] To achieve the above purpose, the technical solution adopted by this application is:

[0006] The present application provides a method for preparing immobilized hyaluronidase, comprising the following steps:

[0007] (1) adding the zinc foam to hydrochloric acid for immersion, and drying to obtain the pretreated zinc foam;

[0008] (2) mixing the hyaluronidase solution, the organic ligand solution and the foamed metal zinc obtained in step (1), and drying to obtain Zn-MOFs / hyaluronidase;

[0009] (3) Immersing the Zn-MOFs / hyaluronidase obtained in step (2) into an adhesive solution, and drying to obtain immobilized hyaluronidase.

[0010] In the technical solution of the present application, the three-dimensional foam metal has ultra-high porosity and can be used as an excellent substrate material. Metal-Organic Frameworks (MOFs) are crystalline materials with periodic network structures and porous characteristics formed by self-assembly of metal ions or metal atom clusters and organic ligands. MOFs materials have the advantages of ultra-high specific surface area, low crystal density, and size and functional adjustability.

[0011] The present application pre-treats the three-dimensional metal foam, utilizes the metal ions therein to bind to the organic ligands, prepares the MOFs material on the three-dimensional metal foam, and realizes the immobilization of the hyaluronidase. The present application innovatively utilizes the metal ions in the three-dimensional metal foam to form the MOFs material, overcomes the shortcomings of the conventional MOFs material being in powder form, easy to lose and difficult to recycle, and forms the MOFs material not only with an ultra-high specific surface area, but also can provide multiple sites for the subsequent immobilization of the hyaluronidase, and the structure is stable and easy to recycle. The present application adds hyaluronidase during the formation of the MOFs material, utilizes the advantage of the adjustable size of the MOFs material, and fixes the hyaluronidase therein in a suitable size during the formation of the MOFs. The prepared immobilized hyaluronidase is highly stable and reusable, and can still maintain a high enzyme activity after multiple uses.

[0012] In some specific embodiments, the concentration of the hydrochloric acid in step (1) is 6-15 wt %.

[0013] In some specific embodiments, the soaking time in step (1) is 5-20 minutes.

[0014] In some specific embodiments, the drying in step (1) is natural air drying at room temperature.

[0015] The purpose of the pretreatment in step (1) in the present application is to form ZnO on the surface of the foamed metal zinc, which is beneficial to the subsequent formation of Zn-MOFs material.

[0016] As a preferred embodiment of the method for preparing the immobilized hyaluronidase described in the present application, the hyaluronidase includes leech hyaluronidase; and the organic ligand solution includes 2-amino-1-methylimidazole solution.

[0017] In some specific embodiments, the Zn-MOFs / hyaluronidase is NH2-ZIF8 / hyaluronidase; and the solvent of the organic ligand solution is water.

[0018] The applicant of the present application found that leech hyaluronidase has the highest compatibility with Zn-MOFs. After immobilization, it can still maintain a high enzyme activity after multiple uses. However, when other hyaluronidases are immobilized using Zn-MOFs materials, the immobilization effect is poor and the stability of the hyaluronidase is low.

[0019] The organic ligand in the present application is selected from 2-amino-1-methylimidazole. The N atom in 2-amino-1-methylimidazole provides atoms for the coordination of Zn, which can make Zn-MOFs easier to generate and the immobilization of hyaluronidase easier.

[0020] In some specific embodiments, the preparation method of the hyaluronidase solution in step (2) is: dissolving the hyaluronidase in a PBS solution, and incubating at room temperature for 20-60 minutes to obtain the hyaluronidase solution.

[0021] As a preferred embodiment of the method for preparing immobilized hyaluronidase described in the present application, in the step (2), the mass ratio of hyaluronidase in the hyaluronidase solution to the foamed metal zinc obtained in the step (1) is (170-270) mg:1 g.

[0022] In the technical scheme of the present application, the mass ratio of hyaluronidase to foamed metal zinc needs to be controlled within a certain range. If the amount of hyaluronidase added is too little, the amount of hyaluronidase fixed in the formed Zn-MOFs is reduced, resulting in a reduced hydrolysis efficiency of immobilized hyaluronidase. If the amount of hyaluronidase added is too much, the site provided by Zn-MOFs is not enough to fix all hyaluronidases, and there are more free hyaluronidases in the solution, causing waste.

[0023] As a preferred embodiment of the method for preparing immobilized hyaluronidase described in the present application, in the step (2), the concentration of the organic ligand solution is 0.02-0.05 mol / L.

[0024] In some specific embodiments, the mixing in step (2) is performed at room temperature, and the mixing time is 8-16 hours.

[0025] In the present application, the purpose of mixing in step (2) is to fix hyaluronidase in Zn-MOFs while forming Zn-MOFs on the surface of the foamed metal zinc.

[0026] In some specific embodiments, the drying in step (2) is freeze-drying or natural air-drying at room temperature.

[0027] As a preferred embodiment of the method for preparing immobilized hyaluronidase described in the present application, in the step (3), the adhesive is an acrylate; preferably, the adhesive is at least one of methyl acrylate, ethyl acrylate, and methyl methacrylate;

[0028] The concentration of the adhesive solution is 1-3 wt %.

[0029] In some specific embodiments, the solvent of the adhesive solution in step (3) is water.

[0030] In some specific embodiments, the Zn-MOFs / hyaluronidase in step (3) is immersed in the adhesive solution for 2-4 hours.

[0031] In some specific embodiments, the drying in step (3) is freeze-drying or natural air-drying at room temperature.

[0032] In some specific embodiments, before the drying step in step (3), a washing step is further included: the immersed Zn-MOFs / hyaluronidase is washed 2-4 times with a PBS solution.

[0033] In some specific embodiments, the concentration of the PBS solution is 0.01-0.03 mol / L, and the pH is 6.3-6.8.

[0034] In the present application, step (2) prepares Zn-MOFs / hyaluronidase, and the binding between Zn-MOFs and hyaluronidase is not strong. During the subsequent enzymatic hydrolysis process, the hyaluronidase is easy to fall off. In the present application, an adhesive is added through step (3) to make the binding between Zn-MOFs / hyaluronidase stronger, which is beneficial to improve the stability of hyaluronidase and improve the repeated use effect of immobilized hyaluronidase.

[0035] The present application provides immobilized hyaluronidase prepared by the above-mentioned preparation method of immobilized hyaluronidase.

[0036] The immobilized hyaluronidase is prepared by the method provided in the present application, and the hyaluronidase can be fixed in the three-dimensional foam metal material through the MOFs material. The use of the immobilized hyaluronidase is very simple and can be used without any carrier or filtering operation. The prepared immobilized hyaluronidase has high activity and good repeatability, which is conducive to the industrial production of low molecular weight hyaluronic acid.

[0037] The present application provides the use of the above-mentioned immobilized hyaluronidase in the preparation of ultra-low molecular weight hyaluronic acid.

[0038] The present application provides a method for preparing ultra-low molecular weight hyaluronic acid, comprising the following steps:

[0039] S1, dissolving high molecular weight hyaluronic acid in water, adding the above-mentioned immobilized hyaluronidase for enzymolysis to obtain an enzymolysis solution;

[0040] S2. The enzymatic hydrolysate is sequentially decolorized, deproteinized, desalted, sterilized and dried to obtain a powder of ultra-low molecular weight hyaluronic acid.

[0041] In some specific embodiments, in step S1, the mass ratio of high molecular weight hyaluronic acid to immobilized hyaluronidase is (1-3):1.

[0042] In some specific embodiments, in step S1, the enzymatic hydrolysis temperature is 40-48° C., and the enzymatic hydrolysis time is 4-8 h.

[0043] In some specific embodiments, in step S1, the mass ratio of high molecular weight hyaluronic acid to water is 1:(6-15).

[0044] In some specific embodiments, in step S1, the molecular weight of the high molecular weight hyaluronic acid is 800 kDa-1400 kDa, preferably 1100 kDa.

[0045] In some specific embodiments, in step S2, the decolorization step is: adding activated carbon to the enzymatic hydrolysate, stirring to decolorize, and filtering to obtain the decolorized enzymatic hydrolysate.

[0046] In some specific embodiments, the amount of activated carbon added is 0.5-2% of the mass of the enzymatic hydrolyzate.

[0047] In some specific embodiments, the stirring bleaching time is 4-10 hours, and the stirring bleaching speed is 80-150 rpm.

[0048] In some specific embodiments, the filtration is filtration through a ceramic membrane.

[0049] In some specific embodiments, in step S2, the deproteinization step is: adding water to the decolorized enzymatic hydrolyzate to obtain a diluted solution, and filtering the diluted solution through an ultrafiltration membrane to obtain a deproteinized enzymatic hydrolyzate.

[0050] In some specific embodiments, the volume ratio of the decolorized enzymatic hydrolysate to water is 1:(0.5-1.5).

[0051] In some specific embodiments, the ultrafiltration membrane is a 3kDa-10kDa ultrafiltration membrane.

[0052] In some specific embodiments, in step S2, the desalting step is: filtering the deproteinized enzymatic hydrolysate through a nanofiltration membrane to obtain a desalted enzymatic hydrolysate.

[0053] In some specific embodiments, the nanofiltration membrane is a 200-500 Da nanofiltration membrane.

[0054] In some specific embodiments, in step S2, the sterilization step is: passing the desalted enzymatic hydrolysate through a microfiltration membrane to obtain a sterilized enzymatic hydrolysate.

[0055] In some specific embodiments, the pore size of the microfiltration membrane is 0.1-0.3 μm.

[0056] In some specific embodiments, in step S2, the drying is spray drying, and the conditions of spray drying are: the inlet air temperature is 100-120°C; the outlet air temperature is 50-70°C.

[0057] The present application also provides ultra-low molecular weight hyaluronic acid prepared by the above-mentioned preparation method of ultra-low molecular weight hyaluronic acid.

[0058] The average molecular weight of the ultra-low molecular weight hyaluronic acid prepared by the preparation method of the present application is 700-1600Da. High performance liquid chromatography analysis shows that the main components of the ultra-low molecular weight hyaluronic acid are hyaluronic acid tetrasaccharide and hyaluronic acid hexasaccharide.

[0059] The present application also provides the use of the above-mentioned immobilized hyaluronidase or the ultra-low molecular weight hyaluronic acid in the preparation of cosmetics.

[0060] Preferably, the ultra-low molecular weight hyaluronic acid is added in an amount of 0.1-50.0 wt % in the cosmetic.

[0061] The ultra-low molecular weight hyaluronic acid prepared in the present application has excellent anti-inflammatory, repairing and anti-wrinkle effects, and is suitable for use in the preparation of cosmetics.

[0062] Compared with the prior art, this application has the following technical effects:

[0063] The present application provides an immobilized hyaluronidase and its preparation method and application in the preparation of ultra-low molecular weight hyaluronic acid. The immobilized hyaluronidase of the present application uses foamed metal zinc as a substrate material, and the hyaluronidase is fixed in Zn-MOFs during the formation of Zn-MOFs on the surface of the foamed metal zinc, thereby improving the stability and reusability of the hyaluronidase. The present application forms a metal organic framework material with Zn metal ions, and Zn-MOFs not only has a high matching property with hyaluronidase, but also Zn is a non-heavy metal material, and hyaluronidase is fixed in Zn-MOFs, which can reduce the toxic effect of metal ions on hyaluronidase, and is conducive to maintaining the activity of hyaluronidase. The present application also uses 2-amino-1-methylimidazole as an organic ligand to prepare Zn-MOFs containing -NH2, and MOFs with -NH2 have the effect of Lewis pH, and -NH2 can be used as an electron-withdrawing group to enrich electrons in functional groups, promote the adsorption of high molecular weight hyaluronic acid in water, and thus be conducive to improving the hydrolysis effect of hyaluronic acid. After preparing Zn-MOFs / hyaluronidase, in order to further enhance the immobilization effect, the Zn-MOFs / hyaluronidase is subsequently acted on by an adhesive, thereby further improving the stability and reuse effect of the immobilized hyaluronidase. The Zn-MOFs prepared by the foamed metal zinc of the present application combines the ultra-high porosity of the three-dimensional foamed metal and the ultra-high specific surface area of ​​Zn-MOFs, which can provide multiple binding points for the immobilization of hyaluronidase, and is conducive to the preparation of immobilized hyaluronidase.

[0064] The immobilized hyaluronidase prepared in the present application has high stability and good reusability, has a good effect on the hydrolysis of high molecular weight hyaluronidase, and can be hydrolyzed to obtain ultra-low molecular weight hyaluronic acid in a short time. The present application adopts leech hyaluronidase to hydrolyze high molecular weight hyaluronidase, and the leech hyaluronidase does not have transglycosidic activity. The obtained products are mainly hyaluronic acid tetrasaccharide and hyaluronic acid hexasaccharide, the final product has few impurities, the non-reducing end of the final product does not contain unsaturated double bonds, the final product has high stability, and has good anti-inflammatory, repair and anti-wrinkle effects, and is suitable for use in the preparation of cosmetics. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 This is a diagram showing the separation results of the product of Example 10. DETAILED DESCRIPTION

[0066] In order to better illustrate the purpose, technical solutions and advantages of the present application, the present application will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0067] In the following examples and comparative examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0068] Unless otherwise specified, all percentages mentioned in this application are by mass percentages.

[0069] The leech hyaluronidase used in the examples and comparative examples of the present application is from Jiangnan University. The preparation method thereof is referred to: Huang, Hao; Liang, Qixing; Wang, Yang; et al, High-level constitutive expression of leech hyaluronidase with combined strategies in recombinant Pichiapastoris; doi: 10.1007 / s00253-019-10282-7.

[0070] The hyaluronidase (derived from bovine testicles) used in the comparative examples of this application was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0071] The preparation method of the 2-amino-1-methylimidazole solution in the present application is: add 2-amino-1-methylimidazole into water, mix well to obtain the 2-amino-1-methylimidazole solution. In the present application, the solvent of the 2-amino-1-methylimidazole solution is water.

[0072] The preparation methods of the terephthalic acid solution and the p-aminobenzoic acid solution in the comparative example of the present application are the same as those of the 2-amino-1-methylimidazole solution.

[0073] The room temperature mentioned in this application is a temperature of 25±5°C.

[0074] Example 1: An immobilized hyaluronidase

[0075] The preparation method of the immobilized hyaluronidase of this embodiment is:

[0076] (1) soaking the foamed zinc metal in a 10 wt % hydrochloric acid solution for 10 min, and drying at room temperature to obtain a pretreated foamed zinc metal;

[0077] (2) dissolving leech hyaluronidase in PBS solution (0.02 mol / L, pH 6.5), incubating at room temperature for 30 min to obtain a hyaluronidase solution; mixing the hyaluronidase solution, 0.03 mol / L 2-amino-1-methylimidazole solution and the foamed zinc pretreated in step (1), reacting at room temperature for 12 h, and freeze-drying to obtain a solid NH2-ZIF8 / hyaluronidase; wherein the mass ratio of hyaluronidase to pretreated foamed zinc is 200 mg:1 g;

[0078] (3) Soak the NH2-ZIF8 / hyaluronidase prepared in step (2) in a 2 wt% methyl acrylate solution for 3 h, rinse with a PBS solution (0.02 mol / L, pH 6.5) for 3 times, and freeze-dry to obtain immobilized hyaluronidase.

[0079] Example 2-7: An immobilized hyaluronidase

[0080] The preparation method of the immobilized hyaluronidase of Examples 2-7 differs from that of Example 1 in only some steps, and the rest are the same as the preparation method of Example 1. The differences between the preparation method of the immobilized hyaluronidase of Examples 2-7 and Example 1 are shown in Table 1.

[0081] Table 1

[0082]

[0083] Note: “--” indicates the same as Example 1.

[0084] The preparation methods of the immobilized enzymes in Examples 2-7 are the same as in Example 1.

[0085] Example 8: An immobilized hyaluronidase

[0086] The preparation method of the immobilized hyaluronidase of this embodiment is:

[0087] (1) soaking the zinc foam in a 15 wt % hydrochloric acid solution for 5 min, and drying at room temperature to obtain a pretreated zinc foam;

[0088] (2) Dissolving hyaluronidase in PBS solution (0.02 mol / L, pH 6.5), incubating at room temperature for 60 min to obtain a hyaluronidase solution; mixing the hyaluronidase solution, 0.045 mol / L 2-amino-1-methylimidazole solution and the foamed metal zinc pretreated in step (1), reacting at room temperature for 8 h, and drying at room temperature to obtain a solid NH2-ZIF8 / hyaluronidase; wherein the mass ratio of hyaluronidase to pretreated foamed zinc is 220 mg:1 g.

[0089] (3) Soak the NH2-ZIF8 / hyaluronidase prepared in step (2) in a 3.5 wt% ethyl acrylate solution for 2 h, rinse twice with a PBS solution (0.02 mol / L, pH 6.5), and freeze-dry to obtain immobilized hyaluronidase.

[0090] Example 9: An immobilized hyaluronidase

[0091] The preparation method of the immobilized hyaluronidase of this embodiment is:

[0092] (1) soaking the zinc foam in a 6 wt % hydrochloric acid solution for 20 min, and drying at room temperature to obtain a pretreated zinc foam;

[0093] (2) Dissolving hyaluronidase in PBS solution (0.02 mol / L, pH 6.5), incubating at room temperature for 20 min to obtain a hyaluronidase solution; mixing the hyaluronidase solution, 0.04 mol / L 2-amino-1-methylimidazole solution and the foamed metal zinc pretreated in step (1), reacting at room temperature for 16 h, and freeze-drying to obtain a solid NH2-ZIF8 / hyaluronidase; wherein the mass ratio of hyaluronidase to pretreated foamed zinc is 180 mg:1 g.

[0094] (3) Soak the NH2-ZIF8 / hyaluronidase prepared in step (2) in a 2.5 wt% methyl methacrylate solution for 4 h, rinse with a PBS solution (0.02 mol / L, pH 6.5) for 4 times, and dry at room temperature to obtain immobilized hyaluronidase.

[0095] Comparative Example 1: An immobilized hyaluronidase

[0096] The difference between the immobilized hyaluronidase in this comparative example and that in Example 1 is that in Comparative Example 1, the foamed metal zinc in Example 1 is replaced with foamed metal copper, and the remaining steps and parameters are the same as those in Example 1.

[0097] Comparative Example 2: An immobilized hyaluronidase

[0098] The difference between the immobilized hyaluronidase in this comparative example and that in Example 1 is that in Comparative Example 2, the 0.03 mol / L 2-amino-1-methylimidazole solution in Example 1 is replaced with a 0.03 mol / L terephthalic acid solution, and the remaining steps and parameters are the same as in Example 1.

[0099] Comparative Example 3: An immobilized hyaluronidase

[0100] The difference between the immobilized hyaluronidase in this comparative example and that in Example 1 is that in Comparative Example 3, the 0.03 mol / L 2-amino-1-methylimidazole solution in Example 1 is replaced with a 0.03 mol / L p-aminobenzoic acid solution, and the remaining steps and parameters are the same as in Example 1.

[0101] Comparative Example 4: An immobilized hyaluronidase

[0102] The difference between the immobilized hyaluronidase in this comparative example and that in the example is that the leech hyaluronidase in example 1 is replaced with hyaluronidase (derived from bovine testicles), and the remaining steps and parameters are the same as those in example 1.

[0103] Comparative Example 5: An immobilized hyaluronidase

[0104] The preparation method of the immobilized hyaluronidase of this comparative example is:

[0105] (1) soaking the foamed zinc metal in a 10 wt % hydrochloric acid solution for 10 min, and drying at room temperature to obtain a pretreated foamed zinc metal;

[0106] (2) dissolving leech hyaluronidase in PBS solution (0.02 mol / L, pH 6.5), incubating at room temperature for 30 min to obtain a hyaluronidase solution; mixing the hyaluronidase solution, 0.03 mol / L 2-amino-1-methylimidazole solution and the foamed metal zinc pretreated in step (1), reacting at room temperature for 12 h, washing with PBS solution (0.02 mol / L, pH 6.5) three times, and freeze-drying to obtain a solid immobilized hyaluronidase; wherein the mass ratio of hyaluronidase to pretreated foamed zinc is 200 mg:1 g.

[0107] The difference between Comparative Example 5 and Example 1 is that the NH2-ZIF8 / hyaluronidase prepared in Comparative Example 5 is not soaked in an adhesive solution, and NH2-ZIF8 / hyaluronidase is directly used as the final product.

[0108] Comparative Example 6: An immobilized hyaluronidase

[0109] The difference between the immobilized hyaluronidase in this comparative example and that in the example is that in comparative example 6, the 2 wt % methyl acrylate solution in example 1 is replaced with a 2 wt % polyethylene oxide solution, and the remaining steps and parameters are the same as in example 1.

[0110] Comparative Example 7: An immobilized hyaluronidase

[0111] The difference between the immobilized hyaluronidase in this comparative example and that in the example is that in comparative example 6, the 2 wt % methyl acrylate solution in example 1 is changed to a 5 wt % methyl acrylate solution, and the remaining steps and parameters are the same as those in example 1.

[0112] Comparative Example 8: An immobilized hyaluronidase

[0113] The difference between the immobilized hyaluronidase in this comparative example and that in the example is that, in comparative example 8, the 0.03 mol / L 2-amino-1-methylimidazole solution in example 1 is changed to a 0.1 mol / L 2-amino-1-methylimidazole solution, and the remaining steps and parameters are the same as those in example 1.

[0114] Example 10: Ultra-low molecular weight hyaluronic acid

[0115] This embodiment provides a method for preparing ultra-low molecular weight hyaluronic acid, comprising the following steps:

[0116] S1: Dissolve 1000 g of high molecular weight hyaluronic acid (molecular weight between 1000-1200 kDa) in 10 L of water, mix well, add 500 g of immobilized hyaluronidase prepared in Example 1 above, perform enzymolysis at 45° C. for 6 h, remove the immobilized hyaluronidase, and obtain an enzymolysis solution.

[0117] S2: Add 1% activated carbon to the enzymolysis solution of step S1, stir at 100rpm for 6h, and obtain a decolorized enzymolysis solution after filtering through a ceramic membrane; add an equal volume of deionized water to the decolorized enzymolysis solution, mix evenly, and obtain a dilution solution, filter the dilution solution through a 5kDa ultrafiltration membrane to remove protein, and the obtained filtrate is the deproteinized enzymolysis solution; filter the deproteinized enzymolysis solution through a 300Da nanofiltration membrane to obtain a desalted enzymolysis solution; filter the desalted enzymolysis solution through a 0.22μm microfiltration membrane to obtain a sterilized enzymolysis solution; spray dry the sterilized enzymolysis solution, and the drying conditions are: inlet air temperature 110°C, outlet air temperature 60°C, to obtain powdered ultra-low molecular weight hyaluronic acid.

[0118] Examples 11-14: Ultra-low molecular weight hyaluronic acid

[0119] The difference between Examples 11-14 and Example 10 is that the temperature and time of enzymatic hydrolysis are different, and the remaining steps and parameters are the same as Example 10. The differences are shown in Table 2.

[0120] Table 2

[0121] Group Enzymatic hydrolysis temperature (℃) Enzymatic hydrolysis time (h) Example 10 45 6 Embodiment 11 40 -- Example 12 48 -- Embodiment 13 -- 4 Embodiment 14 -- 8

[0122] Note: “--” indicates the same as Example 10.

[0123] Comparative Example 9

[0124] The difference between Comparative Example 9 and Example 10 is that in Comparative Example 9, the immobilized hyaluronidase in Example 10 is replaced with free leech hyaluronidase, and the remaining steps and parameters are the same as Example 10.

[0125] Comparative Example 10

[0126] The difference between Comparative Example 10 and Example 10 is that the enzyme used in Comparative Example 10 is free leech hyaluronidase, the enzymatic hydrolysis temperature is 38° C., the enzymatic hydrolysis time is 12 h, and the remaining steps and parameters are the same as Example 10.

[0127] Comparative Example 11

[0128] The difference between Comparative Example 11 and Example 10 is that in Comparative Example 11, the immobilized hyaluronidase in Example 10 is replaced with commercially available hyaluronidase (derived from bovine testicles), the enzymatic hydrolysis temperature is 38° C., the enzymatic hydrolysis time is 12 h, and the remaining steps and parameters are the same as Example 10.

[0129] Comparative Example 12

[0130] The difference between Comparative Example 12 and Example 10 is that in Comparative Example 12, the immobilized hyaluronidase in Example 10 is replaced by the immobilized hyaluronidase in Comparative Example 4, and the remaining steps and parameters are the same as those in Example 10.

[0131] Comparative Example 13

[0132] The difference between Comparative Example 13 and Example 10 is that in Comparative Example 13, the immobilized hyaluronidase in Example 10 is replaced by the immobilized hyaluronidase in Comparative Example 5, and the remaining steps and parameters are the same as those in Example 10.

[0133] Test Example 1: Immobilization Effect Test

[0134] Test samples: immobilized hyaluronidase of Examples 1-9 and Comparative Examples 1-8.

[0135] Test steps: 10g of the test sample was placed in a shake flask, 50mL of PBS solution (0.02mol / L, pH 6.5) was added, and the shake flask was shaken at 100rpm for 1h. After the test, the concentration of free hyaluronidase in the supernatant was tested. The concentration of free hyaluronidase in the supernatant was used to characterize the immobilization effect of the immobilized hyaluronidase. The higher the concentration of free hyaluronidase in the supernatant, the worse the immobilization effect of the immobilized hyaluronidase.

[0136] Among them, the test method for the concentration of hyaluronidase is:

[0137] (a) Dilute the 250μg / mL standard bovine serum albumin (BSA) solution with deionized water to standard solutions of different concentrations from 0 to 500μg / mL, use a protein kit to determine the protein content, and then mix solution A and solution B in the kit in a ratio of 50:1 to prepare the working solution required for the color reaction. Take 20μL of the prepared standard solution and add 400μL of the working solution, shake well, react in a 60℃ water bath for 30 minutes, and then quickly cool with running water. Measure its absorbance value at a wavelength of 562nm on a UV spectrophotometer within 10 minutes, and draw a protein standard curve with the x-axis as the absorbance value and the y-axis as the protein concentration.

[0138] (b) Take 20 μL of the supernatant after shaking the above test sample and dilute it, repeat the steps in (a) to test the absorbance of the supernatant, and calculate the concentration of hyaluronidase in the supernatant by the above standard curve method. The test results are shown in Table 3 below.

[0139] Table 3

[0140]

[0141] The test results show that, compared with comparative examples 1-6 and 8, the immobilized hyaluronidase of the present application embodiment is shaken, and the free hyaluronidase is less, indicating that the Zn-MOFs of the embodiment have a good immobilization effect on hyaluronidase. Among them, the immobilization effect of the immobilized hyaluronidase of embodiment 1-9 is better than that of comparative example 1, indicating that the type of metal, i.e., the type of MOFs, has a great influence on the immobilization effect of hyaluronidase, and the preferred Zn-MOFs of the present application immobilizes hyaluronidase. The immobilization effect of the immobilized hyaluronidase of embodiment 1-9 is better than that of comparative examples 2 and 3, indicating that the type of ligand affects the immobilization effect of hyaluronidase. The type of ligand affects the type of Zn-MOFs finally generated, affects the stacking structure of Zn-MOFs and its compatibility with hyaluronidase, and finally affects the immobilization effect of hyaluronidase. The present application preferably uses 2-amino-1-methylimidazole as a ligand, i.e., NH2-ZIF8 has a good effect on hyaluronidase.

[0142] The immobilization effect of the immobilized hyaluronidase of Example 1-9 is better than that of Comparative Example 4, indicating that the type of hyaluronidase affects its compatibility with Zn-MOFs, and the conformations, active sites, etc. of different hyaluronidases are all different. In the present application, the leech hyaluronidase has the best compatibility with Zn-MOFs and the best immobilization effect. The immobilization effect of the immobilized hyaluronidase of Example 1-9 is better than that of Comparative Examples 5 and 6, indicating that the addition of the adhesive and the type of the adhesive will affect the immobilization effect of the immobilized enzyme. The immobilization effect of the immobilized hyaluronidase of Example 1-9 is better than that of Comparative Example 8, indicating that the concentration of the ligand affects the formation process of Zn-MOFs, and ultimately affects the immobilization effect of hyaluronidase, the concentration of 2-amino-1-methylimidazole of Comparative Example 8 is too high, and the pore size during the formation process of Zn-MOFs changes, resulting in a low compatibility of hyaluronidase with Zn-MOFs, and the immobilization effect of the final product is poor.

[0143] Test Example 2: Thermal Stability Test

[0144] Test samples: immobilized hyaluronidase of Examples 1-9 and Comparative Examples 1-8.

[0145] Control group: unimmobilized leech hyaluronidase.

[0146] The test samples were immersed in deionized water at 35°C, 45°C and 55°C for 2 hours, respectively, and the enzymatic activity of hyaluronidase before and after immersion was tested. The enzymatic activity of unimmobilized leech hyaluronidase immersed at 35°C for 10 minutes was taken as 100%, and the relative enzymatic activity of the test samples at different temperatures was calculated.

[0147] The test results are shown in Table 4 below.

[0148] Table 4

[0149]

[0150]

[0151] From the results at 35°C (immersion for 10 minutes) in Table 4, it can be seen that the Zn-MOFs in the examples of the present application have a good immobilization effect on leech hyaluronidase. Compared with free leech hyaluronidase, the activity of hyaluronidase is less reduced after immobilization of leech hyaluronidase, especially in Example 1, which is less than 5% lower than the activity of free leech hyaluronidase; while the activity loss of the immobilized hyaluronidase in the comparative example is more than 12%.

[0152] Comparing the results of 35 ° C (immersion 10min) in Table 4, the activity of the immobilized enzyme of Example 1 is higher than that of Comparative Examples 1-4, indicating that in the process of immobilization, the type of metal, the type of ligand and the type of enzyme have an impact on the immobilization effect of the product. In this application, the immobilized MOFs are preferably Zn-MOFs, the ligand is preferably amino 2-amino-1-methylimidazole, and the hyaluronidase is preferably leech hyaluronidase. The activity of the immobilized enzyme of Example 1 is higher than that of Examples 6, 7, and Comparative Examples 5-7, indicating whether the addition of adhesive, the type of adhesive and its concentration have an impact on the immobilization effect of hyaluronidase. In this application, it is best to select an acrylic organic compound as the adhesive. Further, the concentration of the adhesive has an impact on the activity of the final product. Without adding an adhesive or adding too little adhesive, hyaluronidase easily falls off from MOFs, resulting in a decrease in overall activity. Too much adhesive is added (Comparative Example 7), and the active site of the hyaluronidase is easily covered, resulting in a decrease in the enzyme activity of the final product. The activity of the immobilized enzyme in Example 1 is higher than that in Comparative Example 8, indicating that the concentration of the ligand affects the immobilization effect of the product. If the concentration of the ligand is too high, the Zn 2+ It is easy to coordinate with the ligand prematurely, which makes it difficult for hyaluronidase to enter MOFs, and hyaluronidase is easy to fall off, ultimately reducing the enzymatic activity of the immobilized enzyme.

[0153] As can be seen from the results of 35°C (soaking for 2h), 45°C (soaking for 2h), and 55°C (soaking for 2h) in Table 4, the immobilized hyaluronidase of the present application has good thermal stability. Good enzyme activity can be maintained at 55°C. The thermal stability of the immobilized enzyme of Example 1 is better than that of Comparative Examples 1-4, indicating that in the process of immobilization, the type of metal, the type of ligand and the type of enzyme affect the immobilization effect of the final product and the thermal stability of the final product. In the present application, when MOFs is Zn-MOFs, the ligand is 2-amino-1-methylimidazole, and the hyaluronidase is leech hyaluronidase, the thermal stability of the immobilized enzyme is the highest. The thermal stability of the immobilized enzyme of Example 1 is better than that of Comparative Examples 5-7, indicating that the addition of the adhesive, the type of adhesive, and the concentration affect the immobilization effect of the enzyme and the thermal stability of the final product. In the present application, the adhesive is preferably an acrylic organic matter, and the concentration is preferably 1-3wt%. The thermal stability of the immobilized enzyme in Example 1 is better than that in Examples 2, 3 and Comparative Example 8, indicating that the concentration of the ligand affects the immobilization effect of the enzyme and the thermal stability of the final product. In the present application, the concentration of the organic ligand is preferably 0.02-0.05 mol / L.

[0154] Test Example 3: Multiple Enzymatic Hydrolysis Test

[0155] Test samples: immobilized hyaluronidase of Examples 1-9 and Comparative Examples 1-8.

[0156] Test steps: 0.1wt% of the test sample was enzymatically hydrolyzed with a 2wt% hyaluronic acid solution with a molecular weight of 800kDa (the enzymatic hydrolysis temperature was 45°C and the enzymatic hydrolysis time was 3h). After the enzymatic hydrolysis, the test sample was washed twice with PBS solution, and the test sample was put into a new enzymatic hydrolysis experiment. The enzymatic hydrolysis experiment was repeated 4 times. The enzymatic activity of the unimmobilized hyaluronidase immersed at 35°C for 10 minutes was taken as 100%, and the relative enzymatic activity of the test sample before enzymatic hydrolysis, after enzymatic hydrolysis once, and after enzymatic hydrolysis five times was calculated.

[0157] The test results are shown in Table 5 below.

[0158] Table 5

[0159]

[0160]

[0161] As shown in Table 5 above, the immobilized enzyme of the embodiment of the present application can still maintain a high enzyme activity after repeated use. After being reused 5 times, the enzyme activity is still maintained at more than 80%. The immobilized hyaluronidase of Example 1 has the best reusability. After 5 times of enzymolysis, the enzyme activity can still be maintained at more than 90%. The reusability of the immobilized enzyme of Example 1 is better than that of Comparative Examples 1-4, indicating that the type of metal, ligand and enzyme type affect the immobilization effect of the final product and affect the thermal stability of the final product. The reusability of the immobilized enzyme of Example 1 is better than that of 5-7, indicating that whether an adhesive is used, the type of adhesive and the concentration of the adhesive will affect the immobilization effect and reusability of the final product. The present application prefers acrylate compounds as adhesives. In addition, by comparing the results of Example 1 and Comparative Example 7 of Test Example 1 and the results of Example 1 and Comparative Example 7 of this test, it can be seen that although adding more adhesive can enhance the immobilization effect of the enzyme in Zn-MOFs and reduce the precipitation of hyaluronidase, the addition of too much adhesive will cause the active site of the enzyme to be covered, and it is difficult for hyaluronidase to exert the enzymatic hydrolysis effect, resulting in poor multiple enzymatic hydrolysis effect of Comparative Example 7. The reusability of the immobilized enzyme in Example 1 is better than that in Comparative Example 8, indicating that the concentration of the ligand affects the immobilization effect of hyaluronidase and the reusability of the final product. In this application, the concentration of the organic ligand is preferably 0.02-0.05 mol / L.

[0162] Test Example 4: Salt resistance test

[0163] The immobilized hyaluronidase was immersed in deionized water and simulated tap water to explore the immobilization effect of the immobilized hyaluronidase.

[0164] Test samples: immobilized hyaluronidase of Examples 1-9 and Comparative Examples 1-8.

[0165] Control group: unimmobilized leech hyaluronidase.

[0166] Simulated tap water: CaCl2 and MgCl2 solutions with a concentration of 500 mg / L.

[0167] Test steps: The test samples were immersed in deionized water and simulated tap water at 35°C, respectively. After immersion for 2 hours, the activity of hyaluronidase in the test samples was measured. The relative activity of the immobilized hyaluronidase was calculated based on the highest activity of the hyaluronidase in the control group.

[0168] The test results are shown in Table 6 below.

[0169] Table 6

[0170]

[0171] The purity of water used in industrial production processes is far less than that of laboratory water; therefore, if an enzyme has a high salt tolerance and can resist the influence of calcium ions and magnesium ions in water (two common metal ions in tap water), it will have high industrial application value.

[0172] As shown in Table 6 above, the immobilized enzyme of the present application embodiment has good salt tolerance, and after soaking in simulated tap water for 2 hours, the activity can be maintained at more than 82%. Comparative Example 1 and Comparative Examples 1-8 show that during the immobilization process, the type of metal, the type and concentration of hyaluronidase, the type and concentration of ligand, the addition of adhesive, the type and concentration of adhesive all affect the immobilization effect of hyaluronidase and the salt tolerance of the final product.

[0173] Effect Example 1: Ultra-low molecular weight low molecular weight hyaluronic acid component test

[0174] Test samples: ultra-low molecular weight hyaluronic acid of Examples 10-14 and Comparative Examples 9-13.

[0175] The component testing includes the determination of the molecular weight of the final product, the separation of the final product and its content analysis.

[0176] (1) The molecular weight of the final product was determined by high performance size exclusion chromatography, as follows:

[0177] (1.1) Establishment of standard curve: Prepare a series of polysaccharide standards with weight average molecular weights of 20000Da, 10000Da, 4000Da, 2000Da, 1000Da, and 500Da. Prepare solutions of the series of polysaccharide standards with mass concentrations of 0.2%, 0.1%, 0.08%, 0.05%, and 0.02% using mobile phase, filter through a 0.22mm filter membrane, inject samples separately, and record the chromatograms and retention times t RThe GPC software automatically converts t R Convert to elution volume and establish a standard curve of elution volume-molecular weight.

[0178] (1.2) Sample molecular weight determination: Prepare solutions of the test sample with mass concentrations of 0.2%, 0.1%, 0.08%, 0.05%, and 0.02%, filter through a 0.22 mm filter membrane, inject the samples separately, and record the chromatograms. Calculate the average molecular weight and its distribution of the samples using the GPC software based on the standard curve.

[0179] (1.3) Chromatographic conditions: Chromatographic column: ZORBX PSM300 gel column (250 mm × 6.2 mm, 5 mm); mobile phase: 0.71% NaCl (containing 0.02% NaN3) solution, filtered through a 0.45 mm filter membrane, flow rate 1 mL / min; column temperature 35°C; injection volume 20 μL.

[0180] (2) The final product was analyzed and separated by ion exchange. The specific method is as follows: Preparation and Biological Activity Study of Tetrasaccharides and Hexasaccharides of Hyaluronic Acid, by Lv Mengxian. Refer to the experimental method section in 2.2 (pages 11-17).

[0181] (3) According to the test results, the final products in the present application are mostly hyaluronic acid tetraose and hyaluronic acid hexaose. Therefore, the contents of these two substances are mainly detected, and the contents of other hyaluronic acids are obtained by subtraction. The final products of Examples 10-14 of the present application, after being separated by ion exchange, respectively obtain purified hyaluronic acid tetraose and hyaluronic acid hexaose, and the purified hyaluronic acid tetraose and hyaluronic acid hexaose are assayed by the carbazole sulfate method, and the specific method is as follows:

[0182] (3.1) Preparation of glucuronic acid solutions of different concentrations: Take 1g / L glucuronic acid standard solution, pipette 0μL, 100μL, 200μL, 300μL, 400μL, and 500μL of the standard solution into 1.5mL PE tubes, and add water to 1mL. Prepare glucuronic acid solutions with concentrations of 10, 20, 30, 40, 50, and 100mg / L, respectively.

[0183] (3.2) Determination of standard curve: Pipette 200 μL of the glucuronic acid solution of different concentrations diluted in (3.1) into 10 mL colorimetric tubes, add 1 mL of borax-sulfuric acid solution to each tube in an ice water bath and shake well, take out and boil in a boiling water bath for 10 min, add 200 μL of carbazole solution and shake well, boil in a boiling water bath for 15 min for color development reaction. Measure the absorbance at 530 nm and draw a standard curve between glucuronic acid concentration and A530.

[0184] (3.3) Pipette 200 μL of sample solution diluted to appropriate concentration into 10 mL colorimetric tubes, add 1 mL of borax-sulfuric acid solution to each tube in an ice water bath and shake well, take out and boil in a boiling water bath for 10 min, add 200 μL of carbazole solution and shake well, and boil in a boiling water bath for 15 min for color development. Measure the absorbance at 530 nm and obtain the sample content according to the standard curve.

[0185] The product separation results of Example 10 are as follows Figure 1 The separation results of the remaining Examples 11-14 and Comparative Examples 9-13 are Figure 1 Similarly, the analysis results of each peak in the figure are shown in Table 7 below.

[0186] Table 7

[0187]

[0188] Note: HA4 refers to hyaluronic acid tetrasaccharide; HA6 refers to hyaluronic acid hexasaccharide.

[0189] The test results show that the immobilized hyaluronidase of the present application example can hydrolyze high molecular weight hyaluronic acid at a higher temperature, and the proportion of hyaluronic acid tetrasaccharide and hyaluronic acid hexasaccharide in the hydrolyzed product is high. Examples 10-14 of the present application can hydrolyze high molecular weight hyaluronic acid at a higher temperature and in a shorter time, greatly shortening the hydrolysis time of low molecular weight hyaluronic acid and reducing the cost of industrial production.

[0190] Comparative example 9 adopts free leech hyaluronidase to be hydrolyzed, because the temperature of enzymolysis is higher, the enzymolysis effect of hyaluronidase is poor, and final product cannot generate hyaluronic acid tetraose and hyaluronic acid hexaose.Comparative example 10 is compared with comparative example 9, and the enzymolysis temperature of free leech hyaluronidase is reduced to 38 degrees Celsius by comparative example 10, and the time of enzymolysis is increased to 12 hours, and free leech hyaluronidase is only hydrolyzed to generate a small amount of hyaluronic acid tetraose and hyaluronic acid hexaose, and enzymolysis efficiency is very low.Comparative example 11 changes the free leech hyaluronidase in comparative example 10 into commercially available hyaluronidase (derived from bovine testicles), and the hydrolysis efficiency of hyaluronic acid tetraose and hyaluronic acid hexaose is lower.Even if commercially available hyaluronidase is subsequently immobilized (Comparative example 12), because the types of enzyme are different, the immobilization effect is poor, and the hydrolysis effect of high molecular weight hyaluronic acid is still very poor. In Comparative Example 13, immobilized hyaluronidase without the action of an adhesive was used for enzymatic hydrolysis. Due to the poor immobilization effect, the hydrolysis efficiency of hyaluronic acid tetrasaccharide and hyaluronic acid hexasaccharide was low.

[0191] Effect Example 2: Anti-inflammatory Effect Test TGFβ1

[0192] Test principle: Inflammation is one of the most common clinical diseases. It is a defense response of the human body to ensure the removal of harmful stimuli and repair damaged tissues. When human immune cells are affected by inflammatory factors, some small molecular weight soluble proteins or peptides that can transmit information between cells and have specific immunomodulatory functions are secreted by the body itself and can participate in or cause inflammatory reactions. These substances are called inflammatory factors, including NO, TNF-ɑ, IL-1, IL-6, IL-8, etc. As an anti-inflammatory factor, TGF-β1 can inhibit the proliferation of T cells and B cells, reduce the expression of major histocompatibility complex (MHC) class II antigens, and reduce local inflammatory reactions. At the same time, TGF-β1 has a certain inhibitory effect on the production of inflammatory factors IL-1α, IL-6, and TNF-α in artificial skin light damage caused by ultraviolet rays, that is, it has a protective effect on the light damage model.

[0193] In this experiment, LPS-induced mouse fibroblasts L929 were used as an in vitro inflammatory cell model, and the relative expression level of the anti-inflammatory factor TGF-β1 mRNA was measured to evaluate whether the test substance had an in vitro anti-inflammatory effect.

[0194] Test sample: The ultra-low molecular weight hyaluronic acid of Examples 10-14 and Comparative Examples 9-13 was prepared into a solution with a mass concentration of 1% using H-DMEM culture medium.

[0195] Test steps: Add 2×10 5 L929 cells were added with H-DMEM medium and cultured at 37°C, 5% CO2, and saturated humidity for 24 hours; the culture medium was discarded, 1 mL of H-DMEM medium was added to the negative control group, and 1 mL of 20 μg / mL LPS solution was added to the model control group and the test sample group for 6 hours to induce modeling, the culture medium was discarded, 1 mL of H-DMEM medium was added to the negative control group and the model control group, and 1 mL of the corresponding sample solution was added to the test sample group, and culture was continued for 24 hours. After the culture, total cell RNA was extracted, and the expression of TGF-β1 mRNA was detected by real-time qPCR. The relative expression of TGF-β1 gene in the negative control group was F=1, and 2 -ΔΔCT The F value of each sample was calculated by this method.

[0196] The test results are shown in Table 8 below.

[0197] Table 8

[0198]

[0199] The test results show that after using the ultra-low molecular weight hyaluronic acid of Examples 10-14 and Comparative Examples 9-13, the relative expression of the anti-inflammatory factor TGF-β1 mRNA in the cell increases, indicating that TGF-β1 production increases, and the inflammatory factors IL-1α, IL-6, and TNF-α are inhibited, and have an anti-inflammatory effect. Among them, the anti-inflammatory effect of Examples 10-14 is better than that of Comparative Example 9, indicating that compared with the free leech hyaluronidase, the product obtained by hydrolysis with immobilized hyaluronidase has a better anti-inflammatory effect, while the free hyaluronidase is easily inactivated at 45°C, and the high molecular weight hyaluronic acid cannot be hydrolyzed well, resulting in poor anti-inflammatory effect of the final product of Comparative Example 9. Although Comparative Example 10 reduces the hydrolysis temperature to a suitable temperature for hydrolyzing hyaluronidase, due to the low hydrolysis temperature, the hydrolysis efficiency of the high molecular weight hyaluronic acid is low, and the anti-inflammatory effect of the final product is poor. Comparative Examples 11 and 12 were hydrolyzed with commercially available free or immobilized hyaluronidase, respectively, but the final hydrolysis effect was poor and the anti-inflammatory effect was poor. The immobilized enzyme in Comparative Example 13 was not reinforced with an adhesive, resulting in poor hydrolysis effect and anti-inflammatory effect of the leech hyaluronidase.

[0200] Effect example 3: Repair effect test

[0201] Test principle: Silent information regulator Sirtuin 1 (SIRT1) is a group of type III protein deacetylases, which is considered to be a new anti-aging protein involved in the regulation of cell aging and inflammation. SIRT1 levels and activity are reduced in cell aging caused by oxidative stress. SIRT1-mediated anti-inflammatory aging mechanisms are related to inflammation, premature cell aging, telomere loss, aging-related secretory phenotypes and regulation of DNA damage response. SIRT1 activation has the potential to attenuate cellular oxidative aging by downregulating oxidative stress-mediated cell aging.

[0202] In this experiment, H2O2-induced L929 cells were used as an in vitro oxidative damage cell model. RNA was extracted from the cells using an RNA extraction kit and reverse transcribed into cDNA. Finally, fluorescent quantitative PCR was performed to detect the expression level of the silent information regulator (SIRT1) of the cell gene, thereby evaluating the repair effect of the test sample.

[0203] The higher the expression level of SIRT1, the faster the cell oxidation is reduced and the better the repair effect of the test sample.

[0204] Test sample: The ultra-low molecular weight hyaluronic acid of Examples 10-14 and Comparative Examples 9-13 was prepared into a solution with a mass concentration of 0.5% using H-DMEM culture medium.

[0205] Test steps: Add 2×10 5L929 cells were added with H-DMEM medium and cultured at 37°C, 5% CO2, and saturated humidity for 24 hours. The 6-well plate was removed, the original culture medium in the well was discarded, and the test sample group and the modeling group were added with culture medium containing H2O2 as a stimulus and cultured for 1 hour, then H2O2 was removed, the test sample group was added with the sample to be tested, and the modeling group and the negative control group were added with culture medium, and cultured in an incubator for 24 hours. The cells in each group were broken and RNA was collected, reverse transcribed into cDNA, and the expression of SIRT1 gene was determined by fluorescence quantitative PCR.

[0206] The test results are shown in Table 9 below.

[0207] Table 9

[0208]

[0209] As shown in Table 9 above, after adding H2O2, oxidative stress occurs in the cells. At this time, the cells increase the relative expression of the SIRT1 gene (modeling group). Therefore, the cell antioxidant receptors begin to accelerate repair to return to the original state. The relative expression of the SIRT1 gene in the sample group is higher than that in the modeling group, indicating that the cells are accelerating repair, indicating that the product has a certain repair effect. Among them, the repair effect of Example 10 is better than that of Comparative Examples 9 and 10, indicating that the immobilized hyaluronidase can increase the temperature of enzymolysis under the condition of ensuring enzyme activity, accelerate the rate of hydrolysis, and improve the repair effect of the final product. The repair effect of Example 10 is better than that of Comparative Examples 11 and 12, and the repair effect of Comparative Example 11 is better than that of Comparative Example 12, indicating that the final product obtained by enzymolysis of immobilized leech hyaluronidase in this application has the best repair effect. Replaced with other enzymes, not only the immobilization effect is poor, but also the repair effect of the final product is poor. The immobilized enzyme in Comparative Example 13 did not use an adhesive to reinforce the hyaluronidase, resulting in poor hydrolysis effect of the leech hyaluronidase and poor repair effect.

[0210] Effect example 4: Anti-wrinkle effect test

[0211] Test principle: Collagen is the most abundant and widely distributed protein in the human body. The protein content in skin cells is as high as 71% or more. It is called "soft gold of skin" and is the main "adhesive" that supports the skin structure. It forms a mesh support with elastic fibers to provide strong support for the dermis. The loss of collagen will make the skin loose and wrinkles increase. Type I collagen (Collagen I, COL1) is the most abundant component in the dermis connective tissue. Enhanced expression of COL1 gene can activate the formation of type I collagen, thereby achieving an anti-wrinkle effect.

[0212] This experiment determines the anti-wrinkle effect of the test sample by judging the promoting effect of the test sample on the synthesis of type I collagen in dermal fibroblasts. The stronger the synthesis ability of type I collagen, the better the anti-wrinkle effect of the test sample.

[0213] Test sample: The ultra-low molecular weight hyaluronic acid of Examples 10-14 and Comparative Examples 9-13 was prepared into a solution with a mass concentration of 1% using H-DMEM culture medium.

[0214] Test steps: Add 2×10 5 Dermal fibroblasts were added with H-DMEM culture medium and cultured for 24 hours at 37°C, 5% CO2, and saturated humidity. The 6-well plate was removed, the original culture medium in the well was discarded, the test sample group was added with the test sample, and the negative control group was added with culture medium, and cultured in an incubator for 24 hours. The cells in each group were broken and RNA was collected, reverse transcribed into cDNA, and the expression of COL1 gene was determined by fluorescence quantitative PCR.

[0215] The test results are shown in Table 10 below:

[0216] Table 10

[0217]

[0218]

[0219] The test results show that the ultra-low molecular weight hyaluronic acid of Examples 10-14 of the present application can increase the relative expression of the cell COL1 gene and has a good anti-wrinkle effect. The anti-wrinkle effect of Example 10 is better than that of Comparative Examples 9 and 10, indicating that the immobilized hyaluronidase can increase the temperature of enzymolysis under the condition of ensuring enzyme activity, accelerate the rate of hydrolysis, and improve the anti-wrinkle effect of the final product. The anti-wrinkle effect of Example 10 is better than that of Comparative Examples 11 and 12, and the anti-wrinkle effect of Comparative Example 11 is better than that of Comparative Example 12, indicating that the anti-wrinkle effect of the final product obtained by enzymolysis of immobilized leech hyaluronidase in this application is the best, and when replaced with other enzymes, not only the immobilization effect is poor, but also the anti-wrinkle effect of the final product is poor. Among them, the anti-wrinkle effect of Comparative Example 11 is better than that of Comparative Example 12, indicating that although Comparative Example 12 immobilizes commercially available hyaluronidase, due to the poor immobilization effect, at a temperature of 45°C, the hyaluronidase is easily inactivated, the enzymolysis effect is very poor, and the anti-wrinkle effect of the final product is worse than that of Comparative Example 11. The immobilized enzyme in Comparative Example 13 did not use an adhesive to reinforce the hyaluronidase, resulting in poor hydrolysis effect of the leech hyaluronidase and poor anti-wrinkle effect.

[0220] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A method for preparing immobilized hyaluronidase, characterized in that: The following steps are involved: (1) adding the zinc foam to hydrochloric acid for immersion, and drying to obtain the pretreated zinc foam; (2) mixing the hyaluronidase solution, the organic ligand solution and the foamed metal zinc obtained in step (1), and drying to obtain Zn-MOFs / hyaluronidase; (3) immersing the Zn-MOFs / hyaluronidase obtained in step (2) into an adhesive solution, and drying to obtain immobilized hyaluronidase; In the step (1), the concentration of hydrochloric acid is 6-15wt%, and the soaking time is 5-20min; In the step (2), the hyaluronidase is leech hyaluronidase, the organic ligand solution is 2-amino-1-methylimidazole solution; the concentration of the organic ligand solution is 0.02-0.05 mol / L; the mixing time in the step (2) is 8-16 hours; The mass ratio of hyaluronidase in the hyaluronidase solution to the foamed metal zinc obtained in step (1) is (170-270) mg: 1 g; In the step (3), the adhesive is acrylate, and the concentration of the adhesive solution is 1-3wt%; The Zn-MOFs / hyaluronidase is immersed in the adhesive solution for 2-4 hours.

2. An immobilized hyaluronidase prepared by the method for preparing immobilized hyaluronidase according to claim 1.

3. Use of the immobilized hyaluronidase as claimed in claim 2 in the preparation of ultra-low molecular weight hyaluronic acid.

4. A method for preparing ultra-low molecular weight hyaluronic acid, characterized in that: The following steps are involved: S1, dissolving high molecular weight hyaluronic acid in water, adding the immobilized hyaluronidase as described in claim 2 for enzymolysis to obtain an enzymolysis solution; S2, sequentially decolorizing, deproteinizing, desalting, sterilizing and drying the enzymatic hydrolyzate, and the obtained powder is ultra-low molecular weight hyaluronic acid; The enzymatic hydrolysis temperature in step S1 is 40-48° C., and the enzymatic hydrolysis time is 4-8 hours.